FLUKTUASI KURS RUPIAH TERHADAP DOLLAR AMERIKA SERIKAT PADA PERIODE TAHUN 1997.I – 2004.IV - Anggyatika Mahda Kurnia; Didit Purnomo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
This study aimed to analyze the fluctuation of the rupiah against the U.S. dollar. The data used in this study are quarterly time series data between the 1997.I to 2004.IV. Analysis tool used in this study is multiple linear regressions using the Error Correction Model (ECM). The results of this study concluded that variables such as exchange rates, inflation, SBI rate and the value of imports is stationary, only money supply variable that is not stationary. Based on the classical assumption was not found problem. Normality test showed normal distribution of Ut, tests of model specification with the Ramsey Reset test indicates the model used is linear. The coefficient of determination (R2) showed that approximately 90.5813 percent of the value of the rupiah against the U.S. dollar be explained by variables in the model. Result analysis by t test found that a significant variable is the money supply, inflation, and the value of imports.